Pulmonary disorders in pregnancy: Bronchiectasis, cystic fibrosis, sarcoidosis and interstitial diseases. (December 2022) - Haines, Alena J.; Middleton, Peter G.
Abstract: This chapter aims to provide expert guidance to obstetricians, general practitioners, allied health staff and women with lung disease about the interactions between pregnancy and different lung diseases. This chapter will cover other airway diseases such as bronchiectasis and cystic fibrosis (CF) together with sarcoidosis and interstitial lung disease (ILD), noting that another chapter covers asthma. The physiological changes which occur in pregnancy, such as the changes in airway physiology, resting ventilation and sleep, are summarised in another chapter. This chapter extends the evidence-based approach and clinical expertise of the recent European Respiratory Society/Thoracic Society of Australia and New Zealand (ERS/TSANZ) taskforce. The papers selected were based on the population (pregnant women with lung disease other than asthma) and the effects of these diseases on risks of pregnancy-associated complications and miscarriages, breastfeeding, nutritional considerations, lung function, long-term maternal outcomes and management considerations during pregnancy. As there are very few randomised control trials in the area, the majority of the literature consists of observational studies (prospective or retrospective), cross-sectional surveys and case series. Other guidelines have also recently been published, which may be helpful to the reader.